2014
DOI: 10.1142/s0219519414500316
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Modeling and Finite Element Analysis of Myxomatous Mitral Leaflet Tissue

Abstract: Although rarely discussed, material modeling of the myxomatous leaflet is considered as the cornerstone of mitral valve finite element analysis. The present study presents an incompressible, hyperelastic constitutive model to characterize myxoid mitral leaflet tissue mechanics. The model incorporates the transversely isotropic response and the layered structure of the tissue. First, an analytical constitutive model for the tissue is developed based on continuum mechanics and layered composites theory. Second, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The ‘trust-region-reflective’ optimization method [58], extensively applied to soft tissue finite strain applications [59]–[61], has been employed in this work. Though the Levenberg-Marquardt algorithm has also been used extensively in soft tissue finite strain material coefficient optimizations [62]–[64], it has known limitations for negative definite Hessian matrices [65], which are overcome when the trust-region-reflective optimization is used.…”
Section: Methodsmentioning
confidence: 99%
“…The ‘trust-region-reflective’ optimization method [58], extensively applied to soft tissue finite strain applications [59]–[61], has been employed in this work. Though the Levenberg-Marquardt algorithm has also been used extensively in soft tissue finite strain material coefficient optimizations [62]–[64], it has known limitations for negative definite Hessian matrices [65], which are overcome when the trust-region-reflective optimization is used.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, only two studies have reported the use of myxomatous leaflet properties in their FE-models [17,24]. In both studies, the mechanical response of myxomatous tissue has been acquired by fitting constitutive models to the experimental data presented by Barber et al [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, the paper did not include any material parameters for the presented constitutive model. In the paper by Zhong et al [24], the constitutive model that was used to fit the experimental data in Barber et al [4] assumes a two layered composite, each layer being reinforced by one family of fiber orthogonal with respect to each other. In the present paper the myxomatous leaflet properties described by Barber et al [4] are fitted to the constitutive Gasser-Ogden-Holzapfel (GOH) model available in the Abaqus material library [25], accounting for the mean leaflet thickness observed in BD patients [2].…”
Section: Introductionmentioning
confidence: 99%